Effect of Green Tea, Coffee, and Cocoa Powder Administration on Antioxidant Enzymes of Liver in Experimental Rat Model - Begum, Qudsia; Begum, Maleeha; Tabassum, Arshia; Mahboob, Tabassum (Indus Journal of Bioscience Research, 2025)
Green tea, coffee, and coca powder are natural products known for their potent antioxidant, chemoprotective, anti-inflammatory, and anti-tumorigenic properties. This study aimed to investigate the effects of green tea, coffee, and coca powder on liver antioxidant enzymes in an experimental rat model using biochemical parameters. Twenty-four male albino Wistar rats were randomly divided into four groups (n=10 per group). Group I (control) received a standard diet and distilled water; Group II was orally administered 1% coffee (1 g/100 mL); Group III received 5% green tea (5 g/100 mL) orally; and Group IV was treated with coca powder at a dose of 1 g/kg body weight orally. The daily intake volumes of green tea, coffee, and coca powder were recorded for Groups II, III, and IV, respectively. The impact of these substances on liver antioxidant enzymes was assessed by measuring oxidative stress markers (tissue malondialdehyde, MDA) and antioxidant enzyme activity (catalase and superoxide dismutase, SOD). The results demonstrated that green tea, coffee, and coca powder effectively restored antioxidant enzyme levels. The study highlights the strong antioxidant properties of these compounds in liver tissue. Furthermore, the findings suggest that the administration of green tea, coffee, and coca powder may offer protective benefits against pathological conditions and mitigate the harmful effects of various hepatotoxic agents.